Cradle-to-gate life cycle inventory and environmental performance of Douglas-fir roundwood production in Germany - González-García, Sara (2018)
Throughout the years, the forest sector (forest activities and forest industries) has received special attention concerning the quantification of its environmental performance. Douglas-fir is a softwood species with multiple industrial applications, high productivity and physiological adaptability. In Europe, Germany is the second most important country in terms of dedicated areas to the cultivation of this tree species. This study aims to assess the environmental impacts associated to Douglas-fir cultivation in Germany under representative management practices, including a detailed life cycle inventory of all the processes performed all over the life cycle of the plantation. The environmental assessment shows that the stand establishment and tending is the main responsible of the environmental impacts due to the constraints related to numerous thinning steps (thinning, roundwood forwarding and loading onto trucks for final distribution) which require the use of large machineries and fossil fuel. The logging stage, which includes the final cutting and the corresponding forwarding and loading into trucks, is the second most important stage with a remarkable contribution to all the environmental categories. Although these hot-spots have also been identified for other forest systems in the literature, the different management practices, system boundaries and intensity of forest systems (frequency of activities) will have a key role on the final environmental assessment. In relative terms, forest management activities performed all over the life cycle of Douglas-fir presents much lower environmental impact in comparison with widely assessed species such as spruce, pine or eucalyptus.